Palm Oil Fuel Ash Fineness in Modifying CBR Characteristics of Peat Soil - Dwina, Dila Oktarise; Abiyoga, Nurza Purwa; Nurdin, Ade (Universitas Islam 45, 2024)
Palm Oil Fuel Ash (POFA) is a waste product from the palm oil industry that often causes environmental problems. Its potential as a pozzolan for soil stabilization has been proven; however, the low CaO content makes it an ineffective sole stabilization material. Some researchers suggest reducing the particle size of pozzolan materials to optimize stabilization. This research aims to evaluate the effectiveness of increasing POFA particle fineness in peat stabilization. The study uses samples stabilized with fine and coarse POFA at 30%, 35%, and 40% of the soil's dry weight. California Bearing Ratio (CBR) tests were conducted after curing for 0, 7, 14, and 28 days. Test results show that the highest CBR values for samples with fine and coarse POFA are 5.48% and 5.80%, respectively, with coarse POFA consistently outperforming fine POFA at all curing times. For samples with the same curing time, the CBR value difference between 30% and 40% POFA is less than 1.00, except for fine POFA at 40% after 28 days, which is 1.25 higher than 30%. However, the performance of peat samples with 40% fine POFA is only comparable to those with 35% coarse POFA after 28 days. Based on these results, it can be seen that POFA is more effective as a filler rather than a pozzolan material for peat soil. As a filler, coarse POFA can better enhance the stability of peat.